Remote Sensing Analysis Using Landsat 8 Data For Lithological Mapping - A Case Study In Mount Penanggungan, East Java, Indonesia - Hendra Bahar; Muhammad Taufik (IPTEK Journal of Proceedings Series, 2017)
Abstract ¾ Mount Penanggungan is one of the volcanoes that located in East Java Province, Indonesia, with the current status is a sleeping volcano. Although Mount Penanggungan is not active, it still make an interesting investigation in geological survey, especially to identify the lithological units, due that less researchers took place in Mount Penanggungan. Geological survey and investigaton can describes the information about physically condition of some land or region, with the result is Lithological Map of Mount Penanggungan. Remote sensing imagery, such as Landsat 8 Satellite imagery data series has been used widely in geology for mapping lithology in general. Remote sensing provides information of the properties of the surface exploration targets that is potential in mapping lithological units. Remote sensing technique are one of the standard procedures in exploration geology, due to it is high efficiency and low cost. Lithological mapping in Mount Penanggungan area is carried out by using Landsat 8 Satellite imagery data with image enhancement techniques, including RGB (red, green, blue) band composite, and combine it with Indonesian Surface Map data that will makes an existing Lithological Map of Mount Penanggungan. The results of this study showed the distribution of the lithological units in Mount Penanggungan, which the units are; vulcanic breccia, tuff breccia, and andesitic lava.